Benzene and Pyridine on Silicon (001): A Trial Ground for Long-Range Corrections in Density Functional Theory - Warschkow, O.; Bennett, J.; Miwa, J.; Lopinski, G.; Rosei, F.; McKenzie, D.; Marks, Nigel (American Chemical Society, 2017)
The adsorption chemistry of benzene and pyridine on the silicon (001) surface is characterized by two prominent adsorbate configurations: a precursor structure bonded to a single Si–Si dimer and a “tight-bridge” configuration that connects two adjacent dimers. We examine here the performance of 20 density functionals in predicting the relative stability of these two configurations. Discrepancies between the predicted and experimentally observed preferred structures highlight the importance of long-range exact-exchange terms in these adsorbate systems. These terms, however, tend to be detrimental to the prediction of adsorption and activation energies. We discuss this conundrum in terms of systematic exchange-correlation errors that scale with the number of molecule–surface bonds.